2019
DOI: 10.2147/opth.s209253
|View full text |Cite
|
Sign up to set email alerts
|

<p>Real-World Data: Ranibizumab Treatment For Retinal Vein Occlusion In The OCEAN Study</p>

Abstract: PurposeThe non-interventional OCEAN study (NCT02194803) evaluated frequency and monitoring of ranibizumab injections for retinal vein occlusion (RVO) in routine practice in Germany.MethodsRVO patients (including branch and central RVO (BRVO/CRVO)) receiving ranibizumab were included. Best-corrected visual acuity (BCVA) testing, imaging and treatment were performed at the investigators’ discretion and documented over 24 months.ResultsOverall, 744 RVO patients (27% BRVO, 16% CRVO, remaining unspecified RVO) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
32
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 30 publications
5
32
2
1
Order By: Relevance
“…Treatments in the present study were withheld when vision was good, which could have led to the fewer treatments and the thickened maculae in our cohort. The visual and anatomic outcomes of CRVO at 12 months in the present study were inferior and the number of treatments fewer than those reported in studies in routine clinical practice [ 15 17 ]. Neovascularization on the retina and iris in our cohort was more frequent than reported in those studies.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Treatments in the present study were withheld when vision was good, which could have led to the fewer treatments and the thickened maculae in our cohort. The visual and anatomic outcomes of CRVO at 12 months in the present study were inferior and the number of treatments fewer than those reported in studies in routine clinical practice [ 15 17 ]. Neovascularization on the retina and iris in our cohort was more frequent than reported in those studies.…”
Section: Discussioncontrasting
confidence: 94%
“…The anatomical outcome mirrored functional outcome in BRVO however, it did not for CRVO which was also observed in a study that evaluated the outcomes of ranibizumab for RVO in routine clinical practice in Denmark [ 14 ]. The mean VA which was worse at baseline in CRVO in the present study remained so at 12 months which was similar to those reported in other observational studies of RVO [ 15 17 ]. There were fewer eyes with VA ≤ 0.3 logMAR (20/40) and more with VA ≥ 1 logMAR (20/200) at 12 months in CRVO than in BRVO.…”
Section: Discussionsupporting
confidence: 92%
“…All these factors lead to potential under-treatment. Similarly, other real world studies have shown annual injection frequency ranging from 3 to 5 in RVO [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 52%
“…The visual and anatomic outcomes of CRVO at 12 months in the present study were inferior and the number of treatments fewer than those reported in studies in routine clinical practice. [15][16][17] Neovascularization on the retina and iris in our cohort was more frequent than reported in those studies. Neovascularization and the need of panretinal laser may be unnecessary in eyes that receive adequate treatment for vascular retinal diseases.…”
Section: Discussionmentioning
confidence: 58%
“…[14] The mean VA which was worse at baseline in CRVO in the present study remained so at 12 months which was similar to those reported in other observational studies of RVO. [15][16][17] There were fewer eyes with VA ≤ 0.3 logMAR (6/12) and more with VA ≥ 1 logMAR (6/60) at 12 months in CRVO than in BRVO. The degree of macular edema and the subsequent photoreceptor damage could have limited visual recovery in CRVO despite the improvement in the mean CST.…”
Section: Discussionmentioning
confidence: 99%